2016
DOI: 10.11118/actaun201563062137
|View full text |Cite
|
Sign up to set email alerts
|

Regional Entrepreneurship Culture and the Business Lifecycle: Patterns from the Moravian-Silesian Region

Abstract: The main goal of the paper is to focus on relationship between business cycle under regional entrepreneurial culture. Many of the trends found were less than positive, although there were some new positive trends that could be identifi ed as a source of sustainability in the area of the connection between the sector of small and medium sized enterprises and the local entrepreneurship environment as well as a source of entrepreneurial culture. Moreover, the frequency of co-operational activities with local gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Baštová et al [65] and Dvouletý and Mareš [66] further demonstrated that the highest density of registered businesses (self-employed individuals and business companies) can be found in the capital Prague, which is expected as the capital is the economic and political centre of the country. Other regional scholars [67][68][69][70][71][72] have highlighted the differences between engagement in entrepreneurship and self-employment across the Czech regions, and they further point out that the activity is most densely concentrated around larger towns and cities. It is also well known that the Czech business activity consists mainly of self-employed individuals [73,74].…”
Section: Entrepreneurial Activity In the Czech Republicmentioning
confidence: 99%
“…Baštová et al [65] and Dvouletý and Mareš [66] further demonstrated that the highest density of registered businesses (self-employed individuals and business companies) can be found in the capital Prague, which is expected as the capital is the economic and political centre of the country. Other regional scholars [67][68][69][70][71][72] have highlighted the differences between engagement in entrepreneurship and self-employment across the Czech regions, and they further point out that the activity is most densely concentrated around larger towns and cities. It is also well known that the Czech business activity consists mainly of self-employed individuals [73,74].…”
Section: Entrepreneurial Activity In the Czech Republicmentioning
confidence: 99%
“…A força, qualidade ou talento dos trabalhadores locais foi destacado em outras pesquisas (Audretsch et al 2012, Šebestová et al, 2015, Subrahmanya, 2017 como atributo determinante do empreendedorismo local. Estas pesquisas foram realizadas, respectivamente, na República Tcheca, Alemanha Ocidental e Bangalore.…”
Section: Discussão Dos Resultadosunclassified
“…In general, entrepreneurship is considered to be an essential factor of economic growth in the European Union (EU) and not only there (Audretsch, 2001;Romero, 2011;Carree et al, 2007;Sternberg, 2012;Amaghouss and Ibourk, 2013;HoltzEakin and Kao, 2003;Lukeš, 2013;Šebestová et al, 2015;Holienka et al, 2016;Rusu and Roman, 2017). In this connection and in the context of a cohesion policy, which aims at stimulation of the economic growth through various activities, the importance of promoting entrepreneurship policy has significantly increased.…”
Section: Introductionmentioning
confidence: 99%